DOSAGE MINIMIZATION OF CHLORINE TO IMPROVE WATER QUALITY AND ITS APPLICABILITY FOR SHRIMP LARVAL REARING OPERATIONS IN HATCHERY - P. Nila Rekha; Soumyabrata Sarkar; R. Nishan Raja; A. Panigrahi; Bhatt Jaimin; S. Rajamanickam; S. Sivagnanam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Administration of higher dosage of chlorine leads to a concern about proper dosage determination for shrimp hatchery operations. Hence, the dosage application needs to be reworked at the present context. Accordingly a Completely randomized design experiment with 6 treatments (control, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm of active chlorine content) with 3 replications was conducted. The water quality and the bacterial load were monitored once in 3 hours continuously. The salient observations of the study was that the exposure time for residual chlorine to be nil for the tank with chlorination of 10 ppm concentration was 6 hours, for 20 ppm and 30 ppm it was 18 hours and for 40 ppm and 50 ppm it was 21 hours. Also the results shows that bacterial load was nil in all the treatments viz. 10 to 50 ppm. The pH of the water gets increased and then stabilized. It could be concluded from the study that the chlorination is required in shrimp hatcheries. But the optimum dosage is 10 ppm for ensuring better water quality in shrimp hatchery which is very much less when compared to the general dose of upto 30 ppm for other purposes. Another experimental trial with three replications was conducted to ascertain the survival of post larvae of P. monodon from PL5 to PL 20 with the 10 ppm active chlorine. The study showed that survival was high in 10 ppm.